PREVALENCE OF BOVINE AND BUBALINE CYSTICERCOSIS IN PUNJAB, PAKISTAN - M. Saeed; A. Z. Durrani; M. A. Khan; A. Maqbool; M. Avais; M. Ijaz; I. Ahmad; M.Younus; K. Mehmood; M. Siddiqa; S. Naz (Journal of Animal and Plant Sciences, 2016)
Cysticercosis is zoonotic disease infecting cattle and buffaloes having worldwide distribution. Prevalence of cysticercosis is more in underdeveloped countries, and people working in abattoirs are at greater risk to contract infection during handling of slaughtered carcass. The present study was carried out to determine the prevalence of cysticercosis in cattle and buffaloes in province of Punjab, Pakistan. A total of 2400 animals (n=800 animals from each of 3 zones of Punjab where n=400 cattle; n=400 buffaloes) were randomly selected and examined through postmortem at public and private abattoirs. The prevalence of cysticercosisin cattle and buffaloes was 2.92% and 3.17%, respectively. The highest prevalence of cysticercosiswas observed in cattle (3.75%) and buffaloes (3.5%) of North Punjab followed by those of South Punjab and Central Punjab. A higher prevalence of cysticercosis was observed in cattle (4.63%) and buffaloes (5%) at public sector abattoirs than at private sector abattoirs, where prevalence of cysticercosiswas 1.52% and 1.67% in cattle and buffaloes, respectively. The prevalence of cysticercosiswas higher in female cattle (3.75%) and female buffaloes (3.83%) than in male animals, which was 2.53% in male cattle and 2.80% in male buffaloes. The frequency analysis showed non-significant difference of prevalence in both male and female. In liver, the highest prevalence was observed both in cattle (31.4%) and buffalo (31.6%). In cattle, other organs like heart, lungs, tongue and esophagus showed prevalence of 22.9, 2.9, 11.4 and 8.6%, respectively while in buffaloes, heart and tongue showed 23.7% prevalence and lungs were affected in 2.6% animals with cysticercosis. Statistically, the difference in prevalence of cysticercosiscysts in different organs of cattle and buffaloes was significantly different (P<0.05). In conclusion, cysticercosis is prevalent in cattle and buffaloes with variable infection in different zones of Punjab province.
Keywords: prevalence; bovine cysticercosis; buffaloes; heart; tongue; Punjab